The Role of Objectification in College Women's Substance Misuse and Sexual Risk. Issue 1 (January 2022) - Ertl, Melissa M.; Sawyer, Jacob S.; Martin, Jessica L.; Brenner, Rachel E.
Sexism and objectification present major challenges for mental and physical health among women. Scholars have called for research to identify mechanisms that underlie these associations as well as to delineate factors to target in prevention and intervention efforts. This study aimed to build on central tenets of objectification theory through its examination of sexist experiences in relation to body surveillance, body shame, depressive symptoms, and the health risk behaviors of substance use (i.e., alcohol and drug misuse) and sexual risk (i.e., condom use and number of sexual partners) among a large sample of college student women. We also examined whether body surveillance, body shame, and depressive symptoms would mediate theorized pathways extended to substance use and sexual risk. A sample of 505 full-time college student women ages 18–26 completed an online survey that assessed their health and behaviors. We used structural equation modeling to test mediation hypotheses. Results largely supported hypotheses, extended objectification theory to sexual risk, and expanded upon past research on objectification in relation to substance use. Notably, results of this study provided a more nuanced knowledge of how objectification may lead to increases in sexual risk when assessed by number of sexual partners (but not condom use). Further research is warranted to understand potential explanatory pathways between sexism, objectification, and sexual risk. Findings can inform prevention and intervention efforts to target body surveillance, body shame, and depressive symptoms to attempt to reduce the burden of sexist experiences on women's health.